Beware of the ambiguous enemy of multisystem inflammatory syndrome in adult (MIS‐A) following Covid‐19 infection or vaccination - Ahmad Al Bishawi (14148810) (2023)
Multisystem Inflammatory Syndrome is a rare and novel clinical presentation described during the evolving COVID-19 pandemic. The condition is usually presenting as a sepsis-like syndrome leading to secondary multi-organ dysfunction post–COVID-19 infection. Although the syndrome has been mainly described in children, rare adults' form has been similarly described. We are describing a 37-year-old female patient presented with fever and neck pain after 1 month of a mild SARS-CoV-2 infection course and 10 days post her second COVID-19 vaccine. Examination demonstrated fever, hypotension, and hypoxemia, in addition to multiple tender cervical lymph nodes. Initial laboratory workup showed evidence of significant inflammation with raised markers, including C-reactive protein, ferritin, and interleukin-6. Extensive evaluation to rule out active infection was done, and all return negative, including repeat SARS-CoV-2 test. Furthermore, cardiac evaluation showed moderately reduced systolic ventricular function. Despite all negative test and supportive measures, the patient continued to deteriorate requiring critical care admission for ionotropic support, non-invasive ventilation in addition to presumptive broad-spectrum antimicrobial management. There was no significant improvement with supportive care until the presentation of multisystem involvement on in the context of a recent history of COVID 19 and negative infective screen was raised. The diagnosis of multisystem inflammatory syndrome-adult form (MIS-A) was embraced, and the patient was commenced on methylprednisolone leading to a dramatic resolution of symptoms both clinically and biochemically with stabilization of vital functions allowing for safe outcomes.  Other Information Published in: Clinical Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/ccr3.5138